Seismic Vulnerability Analysis of High-Rise SRCFrame-RC Core Tube Hybrid Construction. (May 2019) - Zhang, Shuyun; Shi, Ting; Ma, Liping
Abstract: With the development of the modern building, the steel-concrete hybrid structure is more and more widely used. However, the study on the seismic behavior of steel reinforced concrete composite structures is not fully studied. Using a 30-storey steel reinforced concrete (SRC) frame-reinforced concrete core tube hybrid structure (RC) analyze the seismic performance and seismic fragility by theoretical analysis and numerical simulation methods. The PUSHOVER method is used to obtain the capacity spectrum curve, the seismic demand spectrum curve and the performance control points. According to the development of plastic hinge of typical structure, the limit value of quantitative index of structure and the division of structural failure grade is determined. According to the data obtained from finite element analysis, the fragility curve. Provide the basis for earthquake disaster prediction and evaluation.